A case study of digital readiness and technology adoption at a theological college in Cape Town, South Africa - Majackie, Collin A (Library and Information Studies Centre (LISC), 2023)
Technological innovations are rapidly transforming the way Higher Educational Institutions are delivering their core mission of teaching, learning and creative inquiry. A significant number of faculty are resistant to adopting new technologies. This study aims to explore the digital readiness and technology adoption of faculty and staff at a theological college and to understand the current digital practices and views of key stakeholders regarding the drivers and barriers of digital readiness and technology adoption. The research aims were met through an extensive literature review and the implementation of a practical research study. A qualitative case study, using semi-structured interviews with key stakeholders was carried out. The findings show that the concepts of digital literacy and digital readiness are often misunderstood. The main driver of technological adoption was COVID-19, while the main barriers were age and the digital divide. Management support was positive, but a clear vision and strategy for technology adoption was absent. The findings offer valuable insight into technological issues that affects HEIs, especially theological education. While findings cannot be generalised, they may be relatable and applicable to other disciplines. Recommendations for future research and practice are proposed for faculty and the college to consider.